Antony and Cleopatra - Goldsworthy, Adrian Keith (New Haven Yale University Press, 2010)
In this dual biography of the two great lovers of antiquity, historian Adrian Goldsworthy goes beyond myth and romance to create a portrait of his subjects--who were first and foremost political animals
The two lands -- The "she-wolf" : Rome's Republic -- The Ptolemies -- The orator, the spendthrift and the pirates -- The oboe player -- Adolescent -- The return of the king -- Candidate -- "The new sibling-loving gods" -- Tribune -- Queen -- Civil war -- Caesar -- Master of horse -- Not king, but Caesar -- Consul -- "One of three" -- Goddess -- Vengeance -- Dionysus and Aphrodite -- Crisis -- Invasion -- "Lover of her fatherland" -- "India and Asia tremble" : the grand expedition -- Queen of kings -- "Is she my wife?" -- War -- Actium -- "A fine deed" -- Conclusion: History and the great romance
Includes bibliographical references (p. 418-454) and index
1
Keywords: Cleopatra -- Queen of Egypt -- -30 B.C; Antonius, Marcus -- 83 B.C.?-30 B.C; Generals -- Rome -- Biography; Queens -- Egypt -- Biography; Statesmen -- Rome -- Biography; Egypt -- History -- 332-30 B.C -- Biography; Egypt -- Kings and rulers -- Biography; Rome -- History -- Republic, 265-30 B.C -- Biography